Peran Manajemen Keuangan Dalam Meningkatkan Kinerja Bisnis Umkm Di Labuhanbatu - Diyana Diyana; Yudi Prayoga (Jurnal Mirai Management, 2023)
This study aims to examine and analyze the role of financial management in SMEs in Labuhanbatu in improving business performance. Data taken based on a number of Umkm Labuhanbatu actors. This research was carried out directly with field surveys to provide questionnaires and interviews to MSMEs. The analytical method used is the quantitative method, with the results showing that the role of financial management both simultaneously and partially has a positive and significant effect on improving the business performance of MSMEs in Labuhanbatu. Keywords: Financial Management, MSMEs, Business Performance